First record of Leucoptera malifoliella (O. Costa, 1836) (Lepidoptera: Lyonetiidae) in Tunisia - Soltani, Rasmi; Rahmouni, Hedi (Bulletin OEPP, 2024)
The leaf blister moth, Leucoptera malifoliella is an invasive pest of apple and other Rosaceae species. It causes significant damage to apple leaves, threatening the production quality and the overall health of the tree. In this paper, we report the first record of L. malifoliella in Tunisia and give details of its distribution in apple orchards of central west Tunisia (Kasserine governorate). After signs of the pest were observed, cocoons were collected from the field and reared until adult eclosion. Identification of the species was based on observations of external morphology in the laboratory in addition to the field diagnosis based on larval damage on leaves. Leucoptera malifoliella was collected firstly in Foussana delegation, then in Sbeitla, Sbiba, Djedliane, Kasserine and Feriana delegations, showing that it is widely spread in the Kasserine governorate. This leaf miner was clearly identified as one of the most abundant pests in some localities. This paper describing the first record of L. malifoliella in central west Tunisia aims to raise awareness on the pest and encourage the collaboration between apple producers, researchers and extension services in the region to establish a programme of monitoring and managing the pest. Premier signalement de Leucoptera malifoliella (O. Costa, 1836) (Lepidoptera: Lyonetiidae) en Tunisie Le cémiostome du pommier Leucoptera malifoliella est un organisme nuisible envahissant affectant la pomme et d‘autres espèces de rosacées. Il cause des dommages importants aux feuilles de pommiers, menaçant la qualité de la production et la santé générale de l‘arbre. Dans cet article, nous rapportons le premier signalement de L. malifoliella en Tunisie et donnons des détails sur sa distribution dans les vergers de pommiers du centre‐ouest de la Tunisie (gouvernorat de Kasserine). Après l‘observation de signes de cet organisme nuisible, des cocons ont été collectés sur le terrain et élevés jusqu‘à l‘éclosion des adultes. L‘identification de l‘espèce est basée sur des observations en laboratoire de la morphologie externe, ainsi que sur le diagnostic sur le terrain basé sur les dommages larvaires sur les feuilles. Leucoptera malifoliella a été collecté d‘abord dans la délégation de Foussana, puis dans les délégations de Sbeïtla, Sbiba, Djedliane, Kasserine et Feriana montrant qu‘il est largement répandu dans le gouvernorat de Kasserine. Cette mineuse de feuilles a été clairement identifiée comme l‘un des organismes nuisibles les plus abondants dans certaines localités. Cet article décrivant le premier signalement de L. malifoliella dans le centre‐ouest de la Tunisie vise à sensibiliser à cet organisme nuisible et à encourager la collaboration entre les producteurs de pommes, les chercheurs et les services de vulgarisation de la région pour établir un programme de surveillance et de gestion de l‘organisme nuisible. Первое обнаружение Leucoptera malifoliella (O. Costa, 1836) (Lepidoptera: Lyonetiidae) в Тунисе Боярышниковая кружковая моль (Leucoptera malifoliella) представляет собой инвазивный вредный организм, развивающийся на яблонях и других видах семейства розоцветных. Его питание наносит значительный вред листьям яблони, угрожая качеству будущего урожая и общему состоянию здоровья дерева. В данной статье сообщается о первом обнаружении L. malifoliella в Тунисе и детально описывается её распространение в яблоневых садах центрального и западного Туниса (провинция Кассерин). После обнаружения признаков присутствия этого вредного организма его коконы были собраны и из них получены имаго. Идентификация вида основывалась на морфологических данных, полученных в лаборатории, а также на полевой диагностике по признакам повреждения листьев личинками. Leucoptera malifoliella была собрана сначала в округе Фуссана, затем в округах Сбейтл, Сбиба, Джедлиана, Кассерина и Фериана, что говорит о её широком распространении в провинции Кассерин. В некоторых местностях этот вид был четко идентифицирована как один из наиболее распространенных вредных организмов. Данная статья описывает первое обнаружение L. malifoliella в центральной и западной частях Туниса и нацелена на повышение осведомленности об этом вредном организме и развитие сотрудничества между производителями яблок, исследователями и информационными службами в регионе для создания программы мониторинга и борьбы с этим вредным организмом.